GAMBARAN GAYA HIDUP ANGGOTA KELUARGA BERISIKO DIABETES MELITUS (DM) TIPE 2 - Lubis, Siti Langga; Utami, Gamya Tri; Dewi, Yulia Irvani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
The lifestyle of a person has a link with the health condition of the person, especially for family members who have risk Diabetes Mellitus (DM) type 2. This study aims to determine the lifestyle of family members at risk of type 2 diabetes with descriptive research design. The sample of this research were 69 respondents taken based on the inclusion criteria using purposive sampling technique. The measuring tools used are questionnaires for smoking habits and eating habits. The analysis of this study were univariate analysis to see frequency distribution in percentage form and narration of the family members at risk of type 2 DM. The results of this research showed that the majority of respondents are in the category of late adolescents (17-25 years) (63,8%), work as a private employee (50,7%), Minangnese (43,5%), have normal weight (50,7%), and family member suffering from DM type 2 that is The respondent's mother (60,9%). Most respondents did not smoke (40.6%) and more than half of respondents had bad eating habits (59,4%). The results of this study indicate that special attention is needed to control the risk of DM type 2 seen from the aspect of eating habits. This study recommends for family members who have a risk of type 2 diabetes to be able to start a healthier life.   Keywords: Eating habit, smoking habit, the risk of type 2 DM.